Porous titanium nitride microspheres on Ti substrate as a novel counter electrode for dye-sensitized solar cells - Wang, G.; Liu, Shaomin (Elsevier, 2015)
Porous titanium nitride (TiN) microspheres film is directly prepared on a Ti substrate by a hydrothermal process in HF solution followed by nitridation in ammonia atmosphere. The prepared porous TiN microspheres film on Ti substrate is applied as a counter electrode for dye-sensitized solar cells. The porous TiN microspheres film displays high electrocatalytic activity for triiodide reduction and Ti substrate presents good electrical conductivity. Consequentially, the combination of these advantages provided by this unique structure (porous TiN film integrated on Ti substrate) confers the as-prepared electrode with excellent photovoltaic performances. Under 100 mW cm−2 irradiation, the dye-sensitized solar cell with this unique structure shows a high conversion efficiency of 6.8%, comparing favorably with the cell based on a conventional Pt counter electrode.